How Thai Language Changes Foreign Student’s Life in Thailand - Krongbuaban, Phra Bandit Pantito (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2019)
This academic paper was aimed to show how Thai language changes life. In other hand, the ministers need foreign labors to participated and visited in Thailand for long-life learning and working in a lifetime adventure in the “Land of Smiles”, its center of Southeast ASEAN countries and other’s nations as well, which attract people over the world to be here. In contraversy, Thai language is the official language in Thailand is an incredible opportunity, then it is the beautiful destination country that offers environmental nature, ocean, delicious food for traveling, the accommodations are diverse, many foreign students need the finance at least a part of their cost of living and study, working. Particularly in Thai society, where superiority is given much importance especially politeness or etiquette are the main manner of the good student’s characteristic to public’s view, everywhere. It will well helps a lot of people in getting a job in a lifetime’s experience. Furthermore, there are many famous international university and International Study Center are as the center for foreigners and foreign students. In recent years, there has been a rapid evolution in the demographics of English communities. Meanwhile, foreign students are also needs English and interested in learning a new language institute picked up their dream in learning and working to receive better opportunities than those who don’t have language proficiency. Additionally, some part of developing countries and territories wholly or partly in Thailand such as Vietnam, Malaysia and China, India, Korea, amongst other countries were interested in speaking a second language can improve their business, money, culture or even cognitive skills and improved social life. Hence, they could have better job opportunities in the future and to further understand the nature of the learning in Thai culture as well as endlessly searching and institutional support foreign student’s challenging in their life.